Influencing Factor of Price, Facilities, and Destination Image on Customer Satisfaction toward Glamping Revisit Intention in Chiang Mai, Thailand - Sukthaworn, Mareema; Nuangjamnong, Chompu (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2024)
Purpose – the purpose of this study is to investigate the influencing factor of Price, Facilities, and Destination image on customer satisfaction toward glamping revisit intention in Chiang Mai, Thailand. and understand the factors that contribute to their revisit intention. Design/Methodology/Approach – This study utilizes both primary and secondary data collection techniques to examine the influencing factor of price, facility, and destination on customer satisfaction toward glamping revisit intention in Chiang Mai, Thailand. The data was gathered from 400 respondents, consisting of glamper in Chiang Mai including both Thai and non-Thai tourists. Additionally, this research draws upon the theoretical framework from previous studies to construct a new conceptual framework. Findings – This study is intended to find the factors influencing customer satisfaction. Followed by investigating the role of customer satisfaction that effect glamping revisit intention among the tourists in Chiang Mai, Thailand. It’s too narrow focus on Chiang Mai restricts the generalizability of its findings to other glamping destinations. Research Limitations/Implications – the limitations of the research displayed several element limits among the price, facilities and destination image on customer satisfaction toward glamping revisit intention in Chiang Mai, Thailand. Narrowly examining only these factors, it overlooks the potential influence of other variables that may impact tourists' choices of glamping locations. Originality/value – This study focuses on influencing factors of price, facilities, and destination image on customer satisfaction toward glamping revisit intention in Chiang Mai, Thailand. Keywords – Price, Facilities, Destination image, customer satisfaction, glamping, revisit intention JEL classification code – L83, M31